Not All Noises Are Equal: Investigating Auditory Distraction in Emergency Care Using the Tesseract Simulation Platform - Du, David; Lau, Nathan; Ojeifo, Olumide A.; Upthegrove, Tanner; Baber, Adam; Jones, Nathan A.; Parker, Sarah H. (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Auditory distractions in clinical environments can impair performance, yet their impact in emergency department (ED) waiting rooms remains understudied. This study investigates how distinct noise types (baby crying, conversations, and equipment alarms) and temporal patterns (continuous vs. intermittent) influence nursing triage performance. Thirty-two ED nurses completed standardized triage tasks within the Tesseract, an immersive audio-visual simulation platform replicating ED waiting room conditions. Preliminary results from 16 participants suggest that the effects of noise depend on both acoustic features and temporal structures. Subjective perceptions of distraction did not consistently align with measured outcomes. This work provides early evidence that auditory distractions influence clinical task execution in complex, task- and context-specific ways, underscoring the need for targeted mitigation strategies and soundscape-aware simulation training.